2020
DOI: 10.1038/s41467-020-18999-0
|View full text |Cite
|
Sign up to set email alerts
|

Fungal oxylipins direct programmed developmental switches in filamentous fungi

Abstract: Filamentous fungi differentiate along complex developmental programs directed by abiotic and biotic signals. Currently, intrinsic signals that govern fungal development remain largely unknown. Here we show that an endogenously produced and secreted fungal oxylipin, 5,8-diHODE, induces fungal cellular differentiation, including lateral branching in pathogenic Aspergillus fumigatus and Aspergillus flavus, and appressorium formation in the rice blast pathogen Magnaporthe grisea. The Aspergillus branching response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 63 publications
4
60
1
Order By: Relevance
“…In conclusion, our study adds to the growing functional importance of oxygenated lipids in fungal biology [ 51 ], and provides new information and insights in implicating fungal jasmonate as a key factor that determines the timely cessation of germ tube growth and precise induction of appressorium formation; and suggests novel cyclic AMP-dependent control points that regulate JA signalling in response to intracellular oxidation in the rice blast pathogen. Future experiments will determine the exact intersection points and mechanistic cooperativity between jasmonate and cAMP signalling; and precise biosensor-based real time analysis of fungal JA to reveal novel/critical targets for controlling the devastating blast disease in rice and other important cereal crops.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In conclusion, our study adds to the growing functional importance of oxygenated lipids in fungal biology [ 51 ], and provides new information and insights in implicating fungal jasmonate as a key factor that determines the timely cessation of germ tube growth and precise induction of appressorium formation; and suggests novel cyclic AMP-dependent control points that regulate JA signalling in response to intracellular oxidation in the rice blast pathogen. Future experiments will determine the exact intersection points and mechanistic cooperativity between jasmonate and cAMP signalling; and precise biosensor-based real time analysis of fungal JA to reveal novel/critical targets for controlling the devastating blast disease in rice and other important cereal crops.…”
Section: Discussionmentioning
confidence: 79%
“…We further found that jasmonates such as 12-OPDA, JA and Me-JA, but not linolenic acid, could induce appressorium formation in the cAMP-signalling defective mutants, suggesting a significant crosstalk between the two signalling moieties. Recently, it was shown that a fungal oxylipin 5,8-diHODE, from Aspergillus fumigatus , has the ability to induce appressorial development in M. oryzae in an in vitro assay [ 51 ]. Constitutively activated PKA in the mac1 -suppressor mutant ( mac1 D sum1-99 ) of M. oryzae , showed increased accumulation of oxilipins (10R)-HPODE and (5S,8R)-DiHODE, likely via the 7,8-Linoleate Diol Synthase (LDS; Jerneren et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Among the endogenous metabolites, higher abundance of linoleate oxylipins in cross-fed Aspergillus cultures might be associated to the fungal resilience under the challenged growth conditions. Recently, Niu et al [23] have suggested the growth modulatory functions of linoleate oxylipin 5,8-DiHODE for regulating the lateral hyphal branching in Aspergillus species. However, we observed a lower abundance of oleate oxylipins in cross-fed Aspergillus cultures suggesting a biosynthetic rewiring of different oxylipins in cross-fed cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Many fungal SMs possess intrinsic functions as components of developmental structures or signals initiating developmental processes. For example, fungal SMs as signaling hormones induce the formation of spores and regulate their germination ( Niu et al, 2020 ; RodrĂ­guez-Urra et al, 2012 ). SMs required for the formation of fungal resting or sexual structures have been identified ( Calvo and Cary, 2015 ; Schindler and Nowrousian, 2014 ; Studt et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%